1994
DOI: 10.1021/ma00087a027
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Small-Angle Neutron Scattering from a Block Copolymer Solution under Shear

Abstract: Small-angle neutron scattering profiles from a concentrated (65 wt % ) polystyrene-polyieoprene block copolymer solution in dioctyl phthalate under shear were obtained both above and below the quiescent order-disorder transition (ODT). The ordered solution has a lamellar structure under quiescent conditions. The shear-induced structure was inferred from scattering measurements in two planes: the v-vxVv plane and the Vv-VXVU plane (v is the fluid velocity direction and Vv is the velocity gradient direction). Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
112
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 21 publications
8
112
0
Order By: Relevance
“…However, the J e values obtained for 3 samples in the disordered state are all higher than those of PS, implying that fluctuation effects are more pronounced for elastic behaviors than for η, qualitatively consistent with previous studies. [15][16][17][18][19] In Therefore, we can conclude that no discontinuity of η 0 and J e occur by ODT for SP melts, consistent with the results for SP solutions.…”
Section: The Values Obtained By Transient Measurements For Sp27supporting
confidence: 87%
See 1 more Smart Citation
“…However, the J e values obtained for 3 samples in the disordered state are all higher than those of PS, implying that fluctuation effects are more pronounced for elastic behaviors than for η, qualitatively consistent with previous studies. [15][16][17][18][19] In Therefore, we can conclude that no discontinuity of η 0 and J e occur by ODT for SP melts, consistent with the results for SP solutions.…”
Section: The Values Obtained By Transient Measurements For Sp27supporting
confidence: 87%
“…15,16) In a few studies, flow induced ordering are reported in the quiescent disordered states close to the ODT. [17][18][19] In the quiescent ordered states, G'(ω ) and G"(ω ) show power law dependence on ω (G', G" ~ ω 1 / 2 ) at the low ω end. 14,15,20) This behavior can be theoretically explained by the large scale motions of randomly oriented grains/defects 21) and/or by chain relaxation mechanism of entangled component polymers (chain retraction modes).…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to know whether or not the melt is homogeneous or heterogeneous, i.e., the position of the order-disorder temperature, TORT, relative to the selected processing temperature, so that the corresponding thermorheologically simple [1] or complex (2,3] behavior can be anticipated. Also of importance is the sensitivity of the order-disorder temperature to changes in process variables such as applied stress or shear rate [4,5]. Finally, it is becoming increasingly apparent that processing a single block copolymer material near ToDr can lead to a variety of morphologies in the final product depending upon the process conditions employed [6, 7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Balzara et. al noticed 18 that in equilibrium the walls of shear cell induce the parallel alignment through the whole 0.5-mm sample, while Laurer et. al observed 19 that under shear there is always a near-surface layer of the parallel lamellae independently of the bulk orientation.…”
mentioning
confidence: 99%
“…To explain the second transition we make use of recent experiments 18,19 and argue that the high-frequency parallel orientation is stabilized by the preferable interaction of the shear-cell walls with on of the components of the melt. Validity of this hypothesis requires further experimental studies.…”
mentioning
confidence: 99%